Capital Flow Management Within Macroeconomics Stability Framework in Indonesia (2008 – 2022) - Kinanthi Sekar Nareswari; Rini Dwi Astuti; Ardito Bhinadi (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
Indonesia is an EMDEs (Emerging Market and Developing Economies) country, and adopting an open economy causes foreign capital flow, especially FDI (Foreign Direct Investment) and PI (Portfolio Investment) can be free flows, and its movements are unpredictable. The movement of capital flows will affect the money supply transmitted to monetary and macroeconomic variables. This study aims to determine the response and contribution of macroeconomic variables to FDI and PI, as well as examining the causality between macroeconomic variables, FDI and PI. This research used the Vector Error Correction Model Granger Causality. The results show that exchange rate and inflation shocks significantly impact FDI and PI. While the results of Granger causality, changes in macroeconomic variables cause changes in FDI and PI. This research recommends that stakeholders continue implementing policy mix and monetary policy to improve exchange rates and inflation stability. In addition, the management of capital flows is still considered because the potential risks posed to the economy are quite large.